Who are the Puritans? ...and what do they teach? - Hulse, Errol (Darlington, UK Evangelical Press, 2000)
Includes bibliographical references and index.
Keywords: Great Britain -- History -- Puritan revolution, 1642-1660.; Puritans -- theology